Biopharmaceutical-Type Chinese Hamster Ovary Cell Cultivation Under Static Magnetic Field Exposure: A Study of Genotoxic Effect - Rekena, Alina; Livkisa, Dora; Kamolins, Edmunds; Vanags, Juris; Loca, Dagnija (Frontiers in Bioengineering and Biotechnology, 2021)
The lack of a sufficient research base is the reason for the ongoing discussion regarding the genotoxic effect of magnetic field exposure on mammalian cell cultures. Chinese hamster ovary (CHO) suspension type cells, that are widely used for biopharmaceutical production, are potentially subjected to an increased magnetic field when cultivated in bioreactors equipped with bottom placed magnetically coupled stirring mechanisms. The main challenge for conducting research in this field remains the availability of a suitable experimental setup that generates an appropriate magnetic field for the raised research question. In the present study, a simple and cost-effective experimental setup was developed that generated a static magnetic field, similar to what has been modelled in large scale bioreactors, and at the same time was suitable for experimental cell cultivation in laboratory conditions. The measured maximum magnetic flux density to which the cells were exposed was 0.66 T. To assess the possible genotoxic effect, cells were continuously sub-cultivated in laboratory petri dishes for a period of 14 days, corresponding to a typical duration of a biopharmaceutical production process in a conventional fed-batch regime. The genotoxic effect was assessed using the cytokinesis block micronucleus (CBMN) assay with fluorescent staining. Results showed that a 0.66 T static magnetic field exposure had no significant long-term effect on cell viability and chromosomal damage but demonstrated a short-term effect on cell apoptosis. Significant increase in nuclear buds formation was observed. These findings may encourage other researchers in future studies investigating cellular responses to magnetic field exposure and contribute relevant data for comparison.